Fictions of African Dictatorship Postcolonial Power Across Genres - Baker, Charlotte; Grayson, Hannah (Peter Lang International Academic Publishing Group, 2017)
Fictions of African Dictatorship examines the fictional representation of the African dictator and the performance of dictatorship across genres. The volume includes contributions focusing on literature, theatre and film, all of which examine the relationship between the fictional and the political. Among the questions the contributors ask: what are the implications of reading a novel for its historical content or accuracy? How does the dictator novel interrogate ideas of veracity? How is power performed and ridiculed? How do different writers reflect on questions of authority in the postcolony, and what are the effects on their stories and modes of narration? This volume untangles some of the intricate workings of dictatorial power in the postcolony, through twelve close readings of works of fiction.